„Księgi Justynine”. O biografii Justine Frank - Magnone, Lena (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The article is devoted to the biography of Justine Frank (1900-1943), a marginalized member of the surrealist movement, a painter and writer who combined Judaism with pornography, a critic of the Zionist project who tragically died in Palestine. Written by an Israeli artist and an expert on the interwar avant-garde, Roee Rosen, it is not only an artistic provocation – a part of a larger experiment in the field of the so-called parafiction also including editions of Frank’s novel Sweet Sweat and exhibitions of her paintings – but also an interesting statement in the discussion on the possibilities and limitations of feminist criticism, as it points out the problem of fabrication of the indispensable precursors.